Electrophysiological correlates of spatial processing during multitasking. (October 2019) - Romeo, Zaira; Bonato, Mario; Zorzi, Marco; Spironelli, Chiara
Abstract: Multitasking is ubiquitous in everyday life. It can have a detrimental effect on several cognitive abilities including spatial processing in both brain-damaged and healthy participants. The present study investigated, in healthy adults, the electrophysiological mechanisms associated with correct detection vs. misdetection of peripheral visual target(s) while processing concurrent visual or auditory stimuli. Correct responses were coupled with increased N1 amplitude under visual (i.e., intra-modal) load but not under auditory (i.e., cross-modal) load. Under visual load, error responses were associated to opposite patterns on N1/N2 components for unilateral and bilateral stimuli. In particular, errors were marked by significantly reduced N1 and N2 amplitude for the left and right visual field, respectively, whereas higher N1 amplitude was found for errors to bilateral targets. This suggests that early negative components represent the biological marker of target awareness under visual load, whereby correct target detection is grounded on a threshold criterion. These results provide an electrophysiological correlate for the allocation of capacity-limited cognitive resources during the concurrent processing of multiple and heterogeneous visual stimuli. Highlights: Multitasking affects behavioral and ERP visuo-spatial processing. The automatic N1 component is modulated by visual attentional load. Omission of visual targets is reflected in the modulation of N1 and N2 components. A threshold criterion seems to be involved in visuo-spatial awareness.